1999
DOI: 10.1101/gr.9.12.1204
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Three Novel Ca2+ Channel γ Subunit Genes Reveals Molecular Diversification by Tandem and Chromosome Duplication

Abstract: Gene duplication is believed to be an important evolutionary mechanism for generating functional diversity within genomes. The accumulated products of ancient duplication events can be readily observed among the genes encoding voltage-dependent Ca2+ ion channels. Ten paralogous genes have been identified that encode isoforms of the α1 subunit, four that encode β subunits, and three that encode α2δ subunits. Until recently, only a single gene encoding a muscle-specific isoform of the Ca2+ channel γ subunit (CAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 55 publications
3
42
0
Order By: Relevance
“…Previous biophysical studies using recombinant Ca 2ϩ channels have indicated an inhibitory role for the ␥ 2 subunit based on changes in the voltage dependence of steady-state inactivation of the channels (3,10). In addition, a recent finding of novel ␥ isoforms (␥ 3 , ␥ 4 , ␥ 5 ) suggests a possibility that a ␥ gene family originated through tandem and chromosome duplication (11). On the other hand, a recent study has suggested a role of the ␥ 2 subunit on the trafficking/clustering of AMPA 1 receptors (12).…”
mentioning
confidence: 99%
“…Previous biophysical studies using recombinant Ca 2ϩ channels have indicated an inhibitory role for the ␥ 2 subunit based on changes in the voltage dependence of steady-state inactivation of the channels (3,10). In addition, a recent finding of novel ␥ isoforms (␥ 3 , ␥ 4 , ␥ 5 ) suggests a possibility that a ␥ gene family originated through tandem and chromosome duplication (11). On the other hand, a recent study has suggested a role of the ␥ 2 subunit on the trafficking/clustering of AMPA 1 receptors (12).…”
mentioning
confidence: 99%
“…On the other hand, two types of trafficking proteins were reported to interact with all (or at least three) AMPA receptor subunits: Narp, a secreted immediate-early gene product that binds to the extracellular portions of the subunit molecule (O'Brien et al, 1999), and the transmembrane AMPA receptor regulatory proteins (TARPs) stargazin/␥2, ␥3, ␥4, and ␥8 . TARPs are four-transmembrane proteins with a weak homology to the ␥ subunits of muscle voltage-dependent Ca 2ϩ channels (VDCCs) (Burgess et al, 1999;Klugbauer et al, 2000). Strikingly, a spontaneous loss of function of stargazin in a mouse mutant (Letts et al, 1998) resulted in failure of synaptic surface expression of AMPA receptors in cerebellar granule cells, in addition to other phenotypic manifestations (Hashimoto et al, 1999;Chen et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent studies have revealed six additional subunits and, hence, there are eight members to date in the VDCCγ family (Black and Lennon., 1999;Burgess et al, 1999Burgess et al, , 2001Klugbauer et al, 2000;Chu et al, 2001;Moss et al, 2002). Each γ subunit contains four putative transmembrane domains with intracellularly located N-and C-termini (Chu et al, 2001;Black, 2003).…”
Section: Introductionmentioning
confidence: 99%